1997
DOI: 10.1021/jp962841r
|View full text |Cite
|
Sign up to set email alerts
|

Electron Injection, Charge Recombination, and Energy Migration in Surface-Modified TiO2 Nanocrystallite Layers. A Laser Photolysis Study

Abstract: Ru(bpy)3 2+ (bpy ≡ bipyridine) and Ru(o-phen)3 2+ (o-phen ≡ o-phenanthroline) have been adsorbed to a membrane layer made of TiO2 nanocrystallites from aqueous solutions at pH 2.5 by means of pretreatment of the surface with Nafion, sodium dodecyl sulfate (SDS) or sodium dodecyl benzyl sulfate (SDBS). Pulsed laser-induced emission and absorbance changes have been studied. The time profiles provide information concerning environmental effects (charge and hydrophobic interactions) on the rates and yields of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…While much discussion in the literature has focused on optimizing the properties of the dye and the redox couples, attention here will be on the properties of TiO 2 as an electron acceptor. Coupling between the excited dye's electronic structure and the TiO 2 CB states is so strong that injection yields approaching 100% have been measured for many different dyes [610,612,622,623,631,633,636,638,640,652]. Another reflection of the strong coupling is that electron injection typically occurs on the sub-picosecond timescale [390,494,601,613,624,628,629,637,638,640,641,643,647,667,669], and in some cases faster than 100 fs [163,198,391,532,536,606,607,609,617,618,625,632,[649][650][651]655,656,662,666].…”
Section: Excited Electron Donor To Tio 2 Conduction Bandmentioning
confidence: 99%
“…While much discussion in the literature has focused on optimizing the properties of the dye and the redox couples, attention here will be on the properties of TiO 2 as an electron acceptor. Coupling between the excited dye's electronic structure and the TiO 2 CB states is so strong that injection yields approaching 100% have been measured for many different dyes [610,612,622,623,631,633,636,638,640,652]. Another reflection of the strong coupling is that electron injection typically occurs on the sub-picosecond timescale [390,494,601,613,624,628,629,637,638,640,641,643,647,667,669], and in some cases faster than 100 fs [163,198,391,532,536,606,607,609,617,618,625,632,[649][650][651]655,656,662,666].…”
Section: Excited Electron Donor To Tio 2 Conduction Bandmentioning
confidence: 99%
“…The dye-sensitization process is based on charge separation at the semiconductor/dye/electrolyte interface . Fast electron injection from the dye to the semiconductor occurs upon illumination followed by hole transfer to the electrolyte solution (regeneration of the dye). Many factors, such as the distance between the dye and the semiconductor, the type of bond that connects them , and the properties of the redox couple in the electrolyte solution, influence the efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Electron transfer from excited-state dyes into nanocrystalline semiconductors (specifically TiO 2 ) and semiconductors particles has recently received a great deal of attention. 1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Most studies have found that this process occurs very quicklys typically in less than a picosecondsalthough in some cases, slower rates are observed. 18 Rapid ET is explained in terms of the large density of acceptor states in the semiconductor conduction band.…”
Section: Introductionmentioning
confidence: 99%
“…Electron transfer from excited-state dyes into nanocrystalline semiconductors (specifically TiO 2 ) and semiconductors particles has recently received a great deal of attention. ,, Most studies have found that this process occurs very quicklytypically in less than a picosecondalthough in some cases, slower rates are observed . Rapid ET is explained in terms of the large density of acceptor states in the semiconductor conduction band. , Although of equal importance in determining the efficiency of charge separation, far less attention has been given to the dynamics of reverse ET.…”
Section: Introductionmentioning
confidence: 99%